The World's Great Classics : Plays by Greek, Spanish, French, German and English Dramatists - Goethe, Johann Wolfgang (autor); Sheridan, Richard Brinsley (autor); Schiller, Friedrich (autor); Ibsen, Henrik (autor); Sardou, Victorien (autor) ((University Collection))
Contiene: Fausto; Los rivales; María Estuardo; Casa de muñecas; Patas de mosca.